MODELLING AND PARAMETER ESTIMATION IN REACTIVE CONTINUOUS MIXTURES: THE CATALYTIC CRACKING OF ALKANES. PART I - PEIXOTO,F. C. (1999)
Fragmentation kinetics is employed to model a continuous reactive mixture. An explicit solution is found and experimental data on the catalytic cracking of a mixture of alkanes are used for deactivation and kinetic parameter estimation.